Efficient 5-Point Block Method for Oscillatory ODEs with Phase Lag and Amplification Error Control - Rubayyi T. Alqahtani; Anurag Kaur; Theodore E. Simos (Mathematics)
This research presents innovative modified explicit block methods with fifth-order algebraic accuracy to address initial value problems (IVPs). The derivation of the methods employs fitting coefficients that eliminate phase lag and amplification error, as well as their derivatives. A thorough stability analysis of the new approach is conducted. Comparative assessments with existing methods highlight the superior effectiveness of the proposed algorithms. Numerical tests verify that this technique significantly surpasses conventional methods for solving IVPs, particularly those exhibiting oscillatory solutions.